Evaluating the Efficacy of Taurodeoxycholic Acid in Providing Otoprotection Using an in vitro Model of Electrode Insertion Trauma - Shah, Viraj; Mittal, Rahul; Shahal, David; Sinha, Priyanka; Bulut, Erdogan; Mittal, Jeenu; Eshraghi, Adrien A. (Frontiers in Molecular Neuroscience, 2020)
Cochlear implants are widely used to provide auditory rehabilitation to individuals having severe to profound sensorineural hearing loss. However, insertion of electrode leads to inner trauma and activation of inflammatory and apoptotic signaling cascades resulting in loss of residual hearing in implanted individuals. Pharmaceutical interventions that can target these signaling cascades hold great potential for preserving residual hearing by preventing sensory cell damage. Bile salts have shown efficacy in various regions of the body as powerful antioxidants and anti-inflammatory agents. However, their efficacy against inner ear trauma has never been explored. The objective of this study was to determine whether taurodeoxycholic acid (TDCA), a bile salt derivative, can prevent sensory cell damage employing an in vitro model of electrode insertion trauma (EIT). The organ of Corti (OC) explants were dissected from postnatal day 3 (P-3) rats and placed in serum-free media. Explants were divided into control and experimental groups: 1) untreated controls 2) EIT 3) EIT+ TDCA (different concentrations). Hair cell density, analyses of apoptosis pathway (cleaved caspase 3), levels of reactive oxygen species (ROS) as well as inducible nitric oxide synthase (iNOS) activity and mitochondrial membrane potential were assayed. Treatment with TDCA provided significant otoprotection against hair cell loss in a dose dependent manner. The molecular mechanisms underlying otoprotection involved decreasing oxidative stress, lowering levels of iNOS, and abrogating generation of cleaved caspase 3. The results of the present study suggest that TDCA provides efficient otoprotection against EIT, in vitro and should be explored for developing pharmaceutical interventions to preserve residual hearing post-cochlear implantation.